Pendidikan Karakter Berbasis Kearifan Lokal Masyarakat Lampung pada Novel Negarabatin: Negeri di Balik Bukit : Negeri di Balik Bukit (2022) - Roma Kyo Kae Saniro; Andina Meutia Hawa; Dyani Prades Pratiwi; Noni Sukmawati (Universitas Serambi Mekkah, 2024)
This research aims to describe the values of local wisdom in the novel Negarabatin: Negeri di Balik Bukit by Udo Z. Karzi (2022). The research method used is descriptive analysis with a literary anthropology approach elaborated with the presence of character education values. The result of the research indicating several values of local wisdom of the Lampung community in their perspective of life. These include the use of the name